2007
DOI: 10.1073/pnas.0704031104
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of spine morphology and spine density by NMDA receptor signaling in vivo

Abstract: Dendritic spines are the major sites of excitatory synaptic transmission in the CNS, and their size and density influence the functioning of neuronal circuits. Here we report that NMDA receptor signaling plays a critical role in regulating spine size and density in the developing cortex. Genetic deletion of the NR1 subunit of the NMDA receptor in the cortex leads to a decrease in spine density and an increase in spine head size in cortical layer 2/3 pyramidal neurons. This process is accompanied by an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
136
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 44 publications
8
136
3
Order By: Relevance
“…Furthermore, acute NMDA receptor antagonism with ketamine has recently been shown to increase spine density, at least transiently, in the cortex (35). In the reports of cell-specific, genetic deletion of NMDA receptors, temporal differences in the developmental stage of Cre expression may explain the variable effects on synapse number (10,11,13,14). With pharmacological studies, it is conceivable that transient and sustained NMDA receptor blockade have opposite effects on synapse function and ultimately on spine density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, acute NMDA receptor antagonism with ketamine has recently been shown to increase spine density, at least transiently, in the cortex (35). In the reports of cell-specific, genetic deletion of NMDA receptors, temporal differences in the developmental stage of Cre expression may explain the variable effects on synapse number (10,11,13,14). With pharmacological studies, it is conceivable that transient and sustained NMDA receptor blockade have opposite effects on synapse function and ultimately on spine density.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, NMDA-type glutamate receptors have long been appreciated for their role in the formation and maintenance of glutamatergic synapses (7), and as mediators of synaptic plasticity (8). Several studies have shown a positive correlation between NMDA receptor activity and spine density (9)(10)(11)(12), with notable exceptions (13,14). However, the molecular mechanisms by which NMDA receptors regulate spine density remain to be fully elucidated.…”
mentioning
confidence: 99%
“…However, patterning in the somatosensory pathway is completely disrupted, an effect observed in the barrel field even when the NR1 deletion is limited to cortex but not thalamus (5). Additionally, cortex-specific NR1 or NR2B deletion has been shown to decrease spine density and alter synapse function in layer 2/3 barrel neurons (21,22). Finally, a recent study used RNAi to knock down NR1 expression in hippocampal pyramidal neurons in organotypic slices and found that compromised NMDA receptor expression decreased net AMPA receptor-mediated input (23).…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for glutamate, especially NMDA receptors, are intimately involved in the early formation of the central nervous system (CNS), being required for neuronal migration (Komuro and Rakic, 1993;Behar et al, 1999), axonal and neurite growth in the foetus and postnatally, neurite extension and branching (Heng et al 1999;Cuppini et al 1999;Rajan and Cline 1998), spine formation and stability (Alvarez et al, 2007;Ultanir et al, 2007), the formation and stability of synapses (Colonnese et al, 2005) and neuronal plasticity (Fagiolini et al,. 2003;Iwasato et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…NMDA receptors have well-established roles in the early migration of neural precursors, neuritogenesis, axonal guidance, spine formation and synapse formation (Colonnese et al, 2005;Komuro and Rakic, 1993;Behar et al, 1999;Heng et al, 1999;Cuppini et al, 1999;Rajan and Cline, 1998;Alvarez et al, 2007;Ultanir et al, 2007). Furthermore, NMDAR contribute to the programmed cell death which shapes the early nervous system by eliminating a proportion of neurons.…”
mentioning
confidence: 99%